IMPROVED DYNAMIC RISK MODEL TO RESTRICT USE IN INFORMATION SYSTEMS OF COMMERCIAL BANKS - Kobiljonov Sh. N. (Innovate Conferences, 2026)
This in the article commerce banks information in systems use restriction in the process risks assessment and management for improved dynamic risk model offer The current risk models statics , types of risk between dependency enough at the level into account not being able to and extreme tail risk assessment of opportunity limitedness This is determined by shortcomings eliminate to grow for the purpose to time associated risk probability and damage level into account recipient functions , inter-risk correlation coefficients , optimal allocation of resources mechanism , VaR and CVaR to the methods based extreme risk analysis and risk again recovery level assessment stages working is issued . Offer commercial model banks information in systems risks dynamic observation , effective management and use restriction mechanisms optimization opportunity gives . From the model use information safety increase, resources reasonable use and emergency to the circumstances preparation to strengthen service does .
Keywords: information security, commerce banks, use limitation, risk model, dynamic risk, VaR, CVaR, tail risk, resources optimization.